The Relationship between Platelet to Lymphocyte Ratio and Platelet Indices with Disease Severity Level of Systemic Lupus Erythematosus - Purbosari Lisnaedy; Umi Solekhah Intansari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Systemic Lupus Erythematosus (SLE) is an episodic, chronic autoimmune inflammatory disease characterized by remission and flare phases. Laboratory parameters required to assess the severity of disease activity in SLE include platelet count and platelet indices. Several studies regarding the Platelet to Lymphocyte Ratio (PLR) and platelet indices on the severity of SLE patients remain inconsistent. This study aimed to evaluate the relationship between PLR value and platelet index with the degree of disease severity in SLE patients. This study used a retrospective analytic observational design in SLE patients from January 2016 to December 2019 at Dr. Sardjito Central Hospital. Disease severity was assessed using the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score. Platelet to Lymphocyte Ratio (PLR) values and platelet indices were measured with a hematology analyzer. The data were analyzed using correlation, bivariate, multiple regression tests, and the ROC curve to determine the PLR cut-off. There were 55 SLE patients with high activity (SLEDAI 11-19; n=30(54,54%)) and very high activity (SLEDAI 20; n=25(45.45%)). There was a significant correlation (p <0.05) between the PLR value, platelet count, plateletcrit, and Mean Platelet Volume (MPV) with SLEDAI scores (p <0.05), but only the MPV variable was significant as an independent variable (p=0.0357). In the ROC curve, a cut-off PLR value of 124 was obtained with a sensitivity of 68.0%, specificity of 66.7%, likelihood ratio=2.04 (AUC=0.659 with p-value=0.035) to detect very high disease activity. Based on the PLR value, platelet count and plateletcrit negatively correlated with SLEDAI score but were related to the very high degree of thrombocytopenia in disease activity. The MPV value reflected the high platelet turnover, which had a positive correlation with the SLEDAI score. Patients with a PLR value ≤124 were 2.04 times more likely to have a SLEDAI score of 20, indicating potential use as a predictor of disease activity. The PLR value and platelet indices were significantly related to the degree of SLE activity.